Repeated-sprint ability in professional and amateur soccer players - Rampinini, E.; Sassi, A.; Morelli, A.; Mazzoni, S.; Fanchini, M.; Coutts, A. J. (Applied Physiology, Nutrition, and Metabolism, 2009)
This study investigated the repeated-sprint ability (RSA) physiological responses to a standardized, high-intensity, intermittent running test (HIT), maximal oxygen uptake (VO2 max)s do not display in the abstract in HTML. For that reason, it is displayed as "V" here, but in the text., and oxygen uptake (VO2) kinetics in male soccer players (professional (N = 12) and amateur (N = 11)) of different playing standards. The relationships between each of these factors and RSA performance were determined. Mean RSA time (RSAmean) and RSA decrement were related to the physiological responses to HIT (blood lactate concentration ([La-]), r = 0.66 and 0.77; blood bicarbonate concentration ([HCO3-]), r = -0.71 and -0.75; and blood hydrogen ion concentration ([H+]),r = 0.61 and 0.73; all p < 0.05), VO2 max (r = -0.45 and -0.65, p < 0.05), and time constant () in VO2 kinetics (r = 0.62 and 0.62, p < 0.05). VO2 max was not different between playing standards (58.5 ± 4.0 vs. 56.3 ± 4.5 mL/kg·min; p = 0.227); however, the professional players demonstrated better RSAmean (7.17 ± 0.09 vs. 7.41 ± 0.19 s; p = 0.001), lower [La-] (5.7 ± 1.5 vs. 8.2 ± 2.2 mmol/L; p = 0.004), lower [H+] (46.5 ± 5.3 vs. 52.2 ± 3.4 mmol/L; p = 0.007), and higher [HCO3-] (20.1 ± 2.1 vs. 17.7 ± 1.7 mmol/L; p = 0.006) after the HIT, and a shorter in VO2 kinetics (27.2 ± 3.5 vs. 32.3 ± 6.0 s; p = 0.019). These results show that RSA performance, the physiological response to the HIT, and differentiate between professional- and amateur-standard soccer players. Our results also show that RSA performance is related to VO2 max, , and selected physiological responses to a standardized, high-intensity, intermittent exercise.